STRATEGIC PROPOSALS FOR INCREASING YOUTH EMPLOYMENT IN THE FACE OF GLOBAL COMPETITION - Meliqulova Dilafruz Muxamadievna (European Science Publishing, 2025)
This article explores strategic proposals aimed at increasing youth employment amidst the challenges posed by global competition. It highlights the importance of innovative approaches to address the skills gap, enhance vocational training, and promote entrepreneurship among young individuals. By examining successful models from various countries and integrating insights from industry stakeholders, the article proposes actionable strategies that governments, educational institutions, and private sectors can implement to create a robust employment landscape for youth. Ultimately, fostering collaboration and adaptability in the labor market emerges as a critical pathway to empower the next generation and build a competitive workforce.
Keywords: Youth employment, global competition, skills gap, vocational training, entrepreneurship, employment strategies, labor market, collaboratio.